Are Asian Migrants Discriminated Against in the Labour Market? : A Case Study of Australia - Satya Paul; P. N. (Raja) Junankar; Wahida Yasmeen (Institute for the Study of Labor (IZA), 2004)
This paper explores the issue of discrimination against Asian migrants in the Australian labour market using a unique panel data set, the Longitudinal Survey of Immigrants to Australia (LSIA). This paper estimates models of the probability of being unemployed for Asian and non-Asian migrants controlling for various characteristics including age, education, and English language ability. More importantly, we control for the visa status of the migrants. Our results suggest that there are significant ?unexplained differences? for males that may be ascribed to ?discrimination? against Asian migrants. However, the results for females are mixed: the evidence suggests that Asian females do worse than non-Asian females only in the first year after arrival.
Keywords: J61; J64; J31; J7; 330; immigrants; discrimination; unemployment; mobility; wage differentials; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Migranten; Asiaten; Lohndifferenzierung; Geschlecht; Schätzung; Australien